2015
DOI: 10.1111/bjd.13507
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and obesity in French children: a case-control, multicentre study

Abstract: This study shows that being overweight with abdominal obesity and being obese is more common in children with psoriasis than in controls. The risk factors are the same as those that affect the French general population, i.e. female sex and having a parent who was overweight. The severity and clinical type of psoriasis do not affect overweight and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 35 publications
3
50
0
1
Order By: Relevance
“…The χ ‐Psocar study was a multicenter, noninterventional, cross–sectional, case‐control study in France of children with psoriasis that evaluated the frequencies of cardiovascular and metabolic comorbidities in children with psoriasis . It was performed in 23 centers from April 1, 2012, to March 30, 2013.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The χ ‐Psocar study was a multicenter, noninterventional, cross–sectional, case‐control study in France of children with psoriasis that evaluated the frequencies of cardiovascular and metabolic comorbidities in children with psoriasis . It was performed in 23 centers from April 1, 2012, to March 30, 2013.…”
Section: Methodssupporting
confidence: 87%
“…The frequencies of metabolic comorbidities were evaluated in children with psoriasis in the Childhood Psoriasis and Cardiovascular comorbidities ( χ ‐Psocar) study, a multicenter, noninterventional, cross‐sectional, case–control study of children with psoriasis, as previously reported . A substudy of baseline data focused on systematically assessed clinical aspects of nail psoriasis is reported herein.…”
mentioning
confidence: 99%
“…In Europe psoriasis affects 0·5–1% of children . The physical, psychological and social impact of psoriasis and the association with comorbidity highlight the need for early management …”
Section: The 261 Treatments Used In the 154 Children: Severity Of Thementioning
confidence: 99%
“…1 Obesity has been linked to the rise and severity of illnesses including diabetes mellitus, hyperlipidemia, cardiovascular disease, cancer, and Alzheimer's disease. 2 Furthermore, obesity has been linked with a chronic lowgrade proinflammatory state and with the development of chronic inflammatory diseases such as rheumatoid arthritis and psoriasis, 3,4 but there is limited and inconclusive information regarding the impact of obesity on inflammatory bowel disease (IBD). 5,6 The major forms of IBD, Crohn's disease (CD) and ulcerative colitis (UC), are lifelong immunologically mediated disorders categorized by chronic inflammation and progressive damage to the gastrointestinal tract, which can contribute to weight loss and patients becoming chronically underweight.…”
mentioning
confidence: 99%